First case with RANBP2 biallelic mutation and severe acute necrotizing encephalopathy phenotype - Ayaz, Akif; Doğru, Zeynep; Kılıç, Betül; Süzek, Barış Ethem (Elsevier B.V., 2022)
Familial acute necrotizing encephalopathy (ANE) is a rapidly progressive encephalopathy that can occur after common viral infections at different stages of life. The clinical findings of 2 siblings diagnosed with ANE were shared and the whole-exome-sequencing study of the index case was performed. It was confirmed by the Sanger method. We found the RANBP2 gene p.I656V variant homozygous in the index case. We found the variant in the parents as heterozygous. We argue that biallelic mutations in the RANBP2 gene may result in ANE with early onset and severe prognosis by increasing penetrance.
First case with RANBP2 biallelic mutation and severe acute necrotizing encephalopathy phenotype br
Keywords: Autosomal Recessive; Biallelic Mutation; Homozygous; P.I656V; RANBP2